Obesity Induced by Neonatal Overfeeding Worsens Airway Hyperresponsiveness and Inflammation - Ye, Zehui; Huang, Ying; Liu, Dan; Chen, Xiaoyi; Wang, Dongjuan; Huang, Daochao; Zhao, Li; Xiao, Xiaoqiu (PLOS ONE, 2012)
Background Obesity is a risk factor for the development of certain respiratory diseases, and neonatal overfeeding results in an early onset of obesity in adulthood. However, the influence of neonatal overfeeding on respiratory diseases has rarely been studied. Therefore, this paper is aimed at investigating the effect of neonatal overfeeding on airway responsiveness and inflammation. Methodology/Principal Findings The neonatal overfeeding was induced by reducing litter size to three pups per litter (small litter, SL) in contrast to the normal litter size with ten pups per litter (NL) on postnatal day 3 (P3) in male ICR mice. On P21, mice were weaned to standard chow diet. Airway responsiveness to methacholine was measured either on P21 or P150. Total and classified inflammatory cells in bronchoalveolar lavage fluid (BALF) were counted, lung inflammatory cells were evaluated through staining with hematoxylin & eosin and F4/80 immunohistochemistry; lung fibrosis was evaluated through staining with Masson and α-SAM immunohistochemistry. Leptin levels in serum were measured by RIA; TNF-α levels in serum and BALF were quantified by ELISA; mRNA levels of TNF-α, CTGF and TGF-β1 in lung tissues were measured using real-time PCR. Mice from SL exhibited accelerated body weight gain, impaired glucose tolerance and hyperleptinemia. Enhanced airway responsiveness to methacholine was observed in SL mice on P150, but not on P21. Pulmonary inflammation was evident in SL mice on P150, as reflected by inflammatory cells especially macrophages around bronchi and interstitium. BALF and serum TNF-α levels and lung TNF-α mRNA expression were significantly increased in SL mice on P150. More collagen accumulated surrounding the bronchi on P150; lung mRNA levels of TGF-β1 and CTGF were also increased on P150. Conclusion In addition to inducing a variety of metabolic defects, neonatal overfeeding enhanced lung inflammation, which may lead to airway remodeling and airway hyperresponsiveness in adulthood.